An impact assessment of the universally accessible cheaper and quality medicine act of 2008 on the medicine prices, technological capability and market shares of the Philippine pharmaceutical industry - Reyes, Jose Ricardo J. (University of the Philippines Diliman, 2009)
The Republic Act 9502, or The University Accessible Cheaper and Quality Medicine Act of 2008, was signed into law by President Gloria Macapagal-Arroyo on June 2008 and was effective on November 2008. Significant provisions include : (1) parallel importation, (2) limitations on patent protection, (3) early working principle, allowing local firms to work on patented drugs, and (4) imposition of Maximum Retail Prices (MRP). Using a Conceptual Framework derived from a Technology Management concepts and models including Structure-Conduct-Performance Model, Porter's Five Forces Model, Marketing Mix Concept, Twiss's Model of Innovation and Forbes and Wield Product Process Proprietary Matrix, this qualitative, exploratory and predictive research study aims to evaluate the impact of the newly implemented Republic Act of 9502 on the Philippine pharmaceutical industry, specifically on medicine prices, local technological capability and market shares. This research shows that Republic Act 9502 will be successful in decreasing medicine prices in the local market mainly due to parallel importation of cheaper products and imposition of price ceilings-by how much and for how long will depend on the political will of the national government. However, Republic Act 9502 does not drive the development of a local technological capability on pharmaceuticals. It may discourage firms from conducting research in the country and shift their focus to marketing and distribution. There may be market share changes in the short term due to the immediate effect of the cheaper alternatives. However, the innovative capabilities of the multinational players will enable them to maintain their dominance of the local market in the long run. The Republic Act 9502 is an immediate political solution to a long standing national problem. In an innovative industry, there is no way to compete but to continuously innovate. A complementary legislation focusing on building the local technological capability may be necessary to achieve a sustainable solution. Only with an innovative domestic technological capability can bring stable low medicine prices and Filipino dominance of the local pharmaceutical industry.